Speech Act Strategies of Customer Service Officers of Internet Provider Company in WhatsApp Group Interactions - Yuli Widiana; Wenny Wijayanti (Journal of linguistics, culture and communication, 2024)
This study investigates the speech act strategies employed by customer service officers (CSO) in an internet provider company while interacting with customers via WhatsApp Group (WAG) chats. The research aims to identify and analyze the types of speech acts used and examine how cultural and digital token factors specific to Javanese communication norms influence these interactions. In 60 days, data was collected from WAG conversations between customer service representatives and clients using the non-participative observation method. Depth interviews were also conducted with the five CSOs. The analysis employed Speech Act Theory and considers the unique context of computer-mediated communication. Results revealed that CSOs frequently utilized commissive speech acts, confirming speech acts, directive speech acts, phatic speech acts, and expressive speech acts with specific purposes. Culturally, the speech acts were employed to maintain harmony and mitigate potential face-threatening situations. The study also highlights how the CSO adapts traditional Javanese communication styles to the digital medium of WhatsApp. Theoretically, these findings contribute to our understanding of cultural pragmatics in professional settings and empirically offer insights for training customer service personnel in culturally diverse contexts. Furthermore, the research underscores the importance of considering cultural nuances in developing effective communication strategies for digital customer service platforms.